NUTRITIONAL QUALITY IN AGRICULTURAL PRODUCTS: ENHANCING FOOD SECURITY THROUGH FUNCTIONAL FOODS AND NUTRIENT-RICH CROPS - Zeynep Toprak; Hale Yilmaz; Ahmad Zamroni (Yayasan Adra Karima Hubbi, 2026)
Food security debates have increasingly shifted from the question of how much food is produced to the question of what nutritional value that food delivers to populations. This study aimed to examine how the nutritional quality of agricultural products, particularly functional foods and nutrient-rich crops, contributes to stronger household food security. A convergent mixed-methods design was employed, combining laboratory analysis of 30 agricultural product samples, household survey data from 150 respondents, and in-depth interviews with 15 key informants drawn from farming, market, and nutrition sectors. The findings showed that nutrient-rich crops and functional food products contained substantially higher levels of protein, iron, zinc, dietary fiber, beta-carotene, and phenolic compounds than conventional staples. Households with greater access to these products reported higher dietary diversity, lower food insecurity scores, and better perceived dietary adequacy. Qualitative evidence further revealed that local processing, market accessibility, nutrition awareness, and community acceptance strengthened the food security effects of nutritionally superior products. Nutritional quality in agricultural products can therefore be understood as a strategic pillar of food security, supporting a shift from quantity-oriented agriculture toward nutrition-sensitive, health-promoting, and more resilient food systems. These findings highlight the need for integrated agricultural, nutritional, and policy interventions across food systems.